Causes for the failures on safety in the rehabilitation - Couto, J. Pedro (2012)
The needs of the country have made that in recent decades the maintenance and rehabilitation of cultural heritage, monumental and housing have been preterit to the new construction. However, as a result of a small bet on quality, a large part of the existing buildings shows needs of intervention. Moreover, the recovery and repopulation of the historic centres of cities is a national call. There is the perspective that rehabilitation arises not only as an attractive "market niche" but also as an important way to rationalizing existing resources. However, the rehabilitation projects management is often faced with various challenges and difficulties, to which is important to find answers. This study aims to analyse the main and specific constraints that hinder the fulfilment of safety conditions in the rehabilitation projects, and about which care should focus in order to mitigate the high level of accidents in this type of activity.